Charting the water regulatory future : issues, challenges and directions - Chaisse, Julien (New horizons in environmental and energy law, 2017)
Water is an essential resource for mankind, yet many countries around the world are currently facing mounting freshwater management challenges, with climate change and new regional imbalances threatening to aggravate this situation further. This timely book offers a unique interdisciplinary inquiry into the issues and challenges water regulation will face in the coming years. The book brings together economists, political scientists, geographers, and legal scholars to offer a number of proposals for the future of water regulation. The contributions in this book are grouped around specific themes. In the Part I, the contributions address the challenges which water poses to public international law. In Part II, the authors explore the most pressing ethical, legal, and social issues. Finally, the discussion in Part III covers the economic drivers shaping the future of water. This discerning book covers all of the primary actors in the water world, including governments, companies, international organizations, and citizens. With an original introduction by the editor and bringing a diverse collection of perspectives into a single collection, the book will be an essential resource for scholars and practitioners in legal and policy fields such as trade and investment, human rights and the environment, as well as in international relations.